Muscular Strength of Upper and Lower Limbs and Self-Esteem in Chilean Schoolchildren: Independent Associations with Body Composition Indicators - Cofre-Bolados, C; Pizarro-Quevedo, T; Suarez-Reyes, M; De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The aim of this study was to analyze the relationship between muscular strength from upper and lower limbs with self-esteem among Chilean schoolchildren, drawing independent associations with body composition indicators. The sample consisted of 1078 schoolchildren. The muscular strength of the upper and lower limbs was evaluated using a digital dynamometer and long jump performance. The general strength index was calculated based on Z-score values. Rosenberg’s test was used to determine the level of self-esteem of participants. Body fat and body mass index were employed as body composition indicators. Boys had significantly more upper and lower strength, and a general strength index higher than girls (11.7 vs. 10.6; 109.7 vs. 97.4; 0.19 vs. -0.24, respectively). For boys and girls combined, there were no significant associations between all muscular strength variables and self-esteem. In boys, upper and lower limb strength was positively associated with self-esteem. In girls, no association between muscular strength and self-esteem was found. In both sexes, the general strength index was not associated with self-esteem. Strategies and programs that promote mental health and muscular strength among schoolchildren, specifically in boys, are needed. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.